(untitled) (Conference Zone, 2022)
In modern medicine, the transition to information technology (IT) provides a number of new opportunities and connection to the digital diagnostic system. This increases the quality of service, shortens examination time, increases the accuracy of diagnosis, creates opportunities for remote consultation, research, remote processing of primary data, and ensures long-term storage of patient information in digital form.